Nutrient Removal by Grain in Modern Soybean Varieties - Esper Neto, Michel; Lara, Lorena Moreira; Maciel de Oliveira, Silas; Santos, Rayssa Fernanda dos; Braccini, Alessandro Lucca; Inoue, Tadeu Takeyoshi; Batista, Marcelo Augusto (Frontiers in Plant Science, 2021)
Knowing the nutrient removal by soybean grain harvest in different varieties, locations and over time is essential to correctly adjust agronomic recommendations, update farmers’ practices and increased nutrient use efficiency. A field-based research trial was carried out to assess macronutrients (N, P, K, Mg, Ca, and S) removed in grain by modern soybean varieties from southern Brazil introduced between from 2007 to 2016. We examined changes between our set of modern varieties and a dataset of historical values encompassing a wide range of varieties introduced before 2007. Moreover, we undertook a synthesis analysis using scientific literature published after 2007 to investigate nutrient removal by grain among modern Brazilian soybeans and a dataset that included field trials from Argentina, the US, and India. There were no yield gains across the years for modern soybean varieties introduced among 2007 and 2016 in Brazil, although the grain N and Mg concentrations decreased. Modern Brazilian soybeans increased nutrient removal compared with that by soybeans historically planted in Brazil, with 11.1, 26.9, 45.0, and 31.6% more N, P, K, and Mg removed, respectively. Our results indicated that soybean growing in Brazil removed 4.3% less N relative to the values reported in the literature dataset, while K removal was 21.4% greater. A significant difference was also recorded for high-yield soybean varieties, and Brazilian varieties removed 11.8% less N and 8.6% more K than varieties in the literature dataset. No differences were found among locations for P removal, averaging 4.9 kg Mg-1 grain. In conclusion, this study indicates that the amounts of nutrients removed by modern soybean varieties were greater relative to the historical values recorded in Brazil, excluding Ca and S. Nonetheless, in the mid-long term (10 years), a significant impact of plant breeding on grain nutrient concentration was recorded only for N and Mg. The difference in nutrient removal patterns between Brazil and other countries indicates an integrated effect of management, genotype and environment on nutrient removal. These findings provide guidance for optimal nutrient management and specific information for plant breeding programs to understand nutrient variability.